CERS-DR : cycle-based ETF rotation strategy with dynamic rebalancing with the application of reinforcement learning and neural network - Miharja, Toni (2019)
It is widely studied and acknowledged that the economy moves in cycles. The business cycle is defined as the natural fluctuation of the economy between periods of expansion and contraction. Following this business cycle, specific industries can outperform or underperform at different phases. As a leading indicator of business cycles, stock price fluctuates in accordance, leading to the development of investment strategies that aim to leverage on this cycle-based price fluctuation. One such investment strategy is the Exchange Traded Fund (ETF) sector rotation strategy, where an investor keeps an investment portfolio consisting of ETFs from different industries and invests in the industry that outperform the rest at the different phases of business cycle. This strategy is increasing in popularity and reputation, making it a significant topic to explore.